"Carbon‐Glue" Enabled Highly Stable and High‐Rate Fe3O4 Nanorod Anode for Flexible Quasi‐Solid‐State Nickel–Copper//Iron Alkaline Battery. Issue 20 (13th August 2018) - Jiang, Yuqi; Zhao, Dengfeng; Ba, Deliang; Li, Yuanyuan; Liu, Jinping
Abstract: The practical application of iron oxide anode in rechargeable alkaline batteries is greatly hampered by the poor electrochemical stability and low rate capability. In addition, flexible solid‐state iron anode‐based rechargeable batteries with distinctive counter electrode coupling are quite lacking. Herein, an interesting "carbon glue" penetration strategy toward Fe3 O4 nanorod film anode is proposed. This design not only immobilizes the nanorods and maintains strong adhesion with the current collector but also ensures continuous electrically conductive pathway, resulting in dramatically increased stability (≈99% capacity retention after 1000 cycles) and excellent rate performance (1.2 min charging with ≈70.6% initial capacity kept). By pairing with a new‐type Ni0.49 Cu0.51 O nanowire array cathode, a unique 1.2 V flexible rechargeable nickel–copper//iron alkaline battery is further assembled, which stores energy based on redox electrochemistry of transition metal ions. It delivers high volumetric energy and power densities (7.21 mWh cm −3 ; 299.30 mW cm −3 ), and demonstrates outstanding stability up to 5000 cycles. In particular, with the utilization of quasi‐solid‐state electrolyte, the device still maintains good performance upon substantially bending and twisting. This work presents a new concept to design high stability iron anode‐based alkaline batteries and further pushes forward the development of emerging flexible energy storage systems. Abstract : "Carbon‐glue" penetration strategy is proposed to immobilize the Fe3 O4 nanorod film anode for strong adhesion with current collector and ensure continuous electrically conductive pathway, dramatically increasing the cycling stability and rate performance. The anode is further assembled with a new‐type Ni0.49 Cu0.51 O nanowire array cathode into a flexible quasi‐solid‐state alkaline battery, delivering high volumetric energy and power densities.